An overview of Capital Market Development Fund-Bursa Research Scheme (CBRS) - Mohammed Qasem, Ameen Ali (American Scientific Publishers, 2015)
Capital Market Development Fund—Bursa Research Scheme (CBRS) which is administered by Bursa Malaysia aims to offer timely information to interested investors about registered listed firms through research done by participating analysts.This paper provides an overview about this scheme, including the trend of the participating listed firms and research houses, since it was introduced in 2005.The detailed analysis shows that the number of participating listed firms and research houses in CBRS declined in the later stage of the scheme, raising concerns over its sustainability.It can be concluded that some of the participating listed firms and research houses discontinued their involvement in the CBRS.The possible reason might be the costs outweigh the benefits enjoyed by the participating firms.